A Cardiac Metastasis of Follicular Thyroid Carcinoma With Partly Squamous Cell Differentiation: Detection in FDG-PET Preceded Visibility on Echocardiography and MRI by More Than a Year. (December 2018) - Stegger, Lars; Rahbar, Kambiz; Schülke, Christoph; Huss, Sebastian; Wenning, Christian
Abstract : Abstract: PET using the radiotracer 18 F-fluorodeoxyglucose (FDG) was performed in a patient who presented with elevated thyroglobulin (Tg) levels several years after initial therapy of follicular thyroid carcinoma (oncocytic variant) and in whom high-dose radioiodine ( 131 I) failed to locate recurrent tumor or to decrease Tg levels. A focal fluorodeoxyglucose uptake in the apical septum of the heart did not have a discernible correlate in echocardiography or MRI for more than 12 months. Finally, a metastasis of the follicular thyroid carcinoma with partly squamous cell differentiation was confirmed and treated by resection and stereotactic body radiotherapy.